2009
DOI: 10.1093/eurjhf/hfp086
|View full text |Cite
|
Sign up to set email alerts
|

A critical comparison of echocardiographic measurements used for optimizing cardiac resynchronization therapy: stroke distance is best

Abstract: AimsDyssynchrony assessment in cardiac resynchronization therapy (CRT) is controversial, and there are no standard protocols for optimizing treatment. We studied the feasibility and reproducibility of several echocardiographic measures to optimize CRT pacemaker settings. We also assessed the utility of 'stroke distance' [left ventricular outflow tract velocity-time integral (LVOT VTI)] in performing this function. Methods and resultsThirty patients underwent the following functional assessments; 6 min walk tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 29 publications
1
44
0
1
Order By: Relevance
“…Although there are sparse and conflicting data on the long-term effect of echoguided AV and VV delay optimization echocardiography remains the most frequently used method for tailoring CRT in clinical practice [5,31]. Thus new methods like the IEGM-based algorithm remains to be compared against this standard, not only with respect to acute hemodynamic effects but also with respect to long-term outcome.…”
Section: Long-term Results Using Iegm-based Optimizationmentioning
confidence: 99%
“…Although there are sparse and conflicting data on the long-term effect of echoguided AV and VV delay optimization echocardiography remains the most frequently used method for tailoring CRT in clinical practice [5,31]. Thus new methods like the IEGM-based algorithm remains to be compared against this standard, not only with respect to acute hemodynamic effects but also with respect to long-term outcome.…”
Section: Long-term Results Using Iegm-based Optimizationmentioning
confidence: 99%
“…Several studies from single centers have shown improvement in cardiac output by echo Doppler-guided AVD optimization [11][12][13]. Doppler parameters used for echoguided optimization include aortic VTI [14,15]; diastolic mitral flow pattern by Ritter's method [16]; iterative method [17]; diastolic filling time [13]; VTI of mitral inflow [18]; Dopplerderived dP/dt [7]; tissue Doppler imaging [11,12]; LV and right ventricular (RV) pre-ejection delays; and myocardial performance index [19].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of stroke volume derived from the left ventricular outflow tract velocity-time integral (VTI) of left ventricular outflow tract (LVOT VTI) has been proposed for optimizing both AV and VV delays [32]. On Figure 3 is echocardiographic presentation of AV optimization and on Figure 4 is shown echocardiographic presentation of VV optimization.…”
Section: Discussionmentioning
confidence: 99%